Dispositivo para la prevención de la aparición de episodios de congelamiento de la marcha y bradicinesia en personas con la enfermedad de parkinso (2021)
This degree work proposes a solution to the problem summarized in the problem or opportunity question (How from industrial design and based on the development of wearables for the biomedical industry, we can prevent, reduce, treat or eliminate episodes of freezing of gait and bradykinesia in people with Parkinson's disease).